Multiple Cases with Probable Treponemal Infection from 16th to 19th Centuries Romania. (24th March 2015) - Radu, C.; Andreica, L.; Constantinescu, M.; Soficaru, A.
Abstract: In this paper, we describe pathological lesions identified in seven skeletons discovered in the Saint Sava necropolis in Bucharest, Romania, dating to the Late Medieval/Early Modern period. The pathological changes observed in the skeletons were analysed using macroscopic examination. Additionally, computed tomography scanning was performed on two individuals displaying advanced lesions on the cranial surface. For the differential diagnosis, we took into consideration treponemal infection, tuberculosis, osteomyelitis, leprosy, fluorosis, melorheostosis, hypertrophic pulmonary osteoarthropathy, Paget's disease and mycotic infection, along with the possibility of multiple afflictions occurring simultaneously. The morphology and distribution of the lesions are suggestive of treponematosis, which, to our knowledge, makes this the first case of this disease on the Romanian territory in archaeological populations. Copyright © 2015 John Wiley & Sons, Ltd.